Effects of 650 nm Diode Laser and 532 nm Frequency-Doubled Q-Switched Nd:YAG Laser on The Growth of Candida albicans, With and Without Photosensitizers - Kazem, Intisar K.; Maki, Amel M. (Iraqi Journal of Laser, 2019)
This work describes an experimental setup to evaluate the photodynamictoxicity of 650 nm diode laser and 532 nm Frequency-doubled Q-Switched Nd:YAG laser on the growth of Candida albicans as well as the potential fungicidal effect when combining the laser irradiation with specific photosensitizers namely methylene blue, toluidine blue, acridine orange and safranin O. In this study the findings showed that the number of colony-forming units per millilitre (CFU/ml) of C. albicans decreased with increasing exposure time. In particular in the case of the frequency doubled Nd:YAG laser combined with safranin O, the best lethal effect occurred at 11 minutes exposure time with 2.26 J/cm² energy density (89.18% reduction) in comparison with the group treated with neither the laser nor with the photosensitizer. Irradiation with the frequency doubled Nd:YAG laser in the presence of acridine orange had less effect in reducing the number of CFU/ml for C. albicans. The highest reduction (85.88%) was achieved with 2.26 J/cm2 energy density at 9 min exposure time. On the other hand, the best performance in the case of diode laser was when combining with methylene blue at 28 minutes exposure and 0.58 w/cm2 power density (45.38%). In the case of diode laser with toluidine blue, the highest reduction of CFU/ml (67.93%) occurred at 35 min at the same power density